Islamic and conventional stocks: Impact of Russia-Ukraine saga on global commodities - Agustin, Isnaini Nuzula; Yulfiswandi, Yulfiswandi; Rehman, Saeeda; Ur Rahman, Haseeb (Jurnal Ekonomi & Keuangan Islam, 2024)
Purpose – This study intends to scrutinize the relationship between oil and gold prices on Indonesia’s Islamic stock market before and during the war between Russia and Ukraine, and compare the nature of sharia and conventional stock during the period of study.Methodology – This study uses daily price data of oil price, gold, Islamic index, and LQ45 index. The period spans from 2020 to 2022, which is split into two sub-periods: pre-war and during the war period. Structural vector autoregression (SVAR) was used for data analysis.Findings – This study provided three main findings. First, the Islamic index was found to be more exogenous than conventional stock, implying the safe haven properties of Islamic stock. Second, oil prices have a negative and significant impact on both conventional and Islamic stocks. However, Islamic stocks are less affected by oil price shocks than conventional stocks. Lastly, Gold is a safe haven asset for both Islamic and conventional stocks.Implications – This study is expected to be beneficial for Islamic investors making investment decisions, particularly in the war period, which is still ongoing and more specific for taking advantage of diversification opportunities.Originality – Despite a huge number of studies that investigate the Islamic stock – oil price nexus, this study uncovers the impact of the most recent geopolitical tension during the Russia-Ukraine War.